English idioms: a cultural consideration - Othman, Khairiah; Abdul Malik, Faridah; Engku Ibrahim, Engku Haliza (2015)
Many advocate that a mastery of idioms is a reflection of native speakers’ proficiency. While idioms are an important part of language, language reflects culture. The aim of the study was to investigate Muslim students’ perspective of English idioms, as to whether there are English idioms which are not in line with the students’ value system. The study employed a qualitative method using document analysis and group discussions. Ninety idioms were chosen and evaluated by Muslim postgraduate students pursuing Master’s degree in English language studies in an Islamic institution. The findings indicate the presence of English idioms which are incongruent with Islamic values, hence the tendency for Muslim learners to view the learning of English negatively. This study has pedagogical implications on teaching English to Muslim students.